Comparative Analysis of Marketing Strategies for Online Shopping Applications on Shopee and Lazada (Case Study of Febi Uinsu Students) - Aris Kukuh Prasetyo; Siti Nur Khalizah Siregar; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
Development in the growing world of business have mande infulencing the world esier. This can be observed in buying goods as desired in a transaction using E-Commerce, regradless of the infulence in the marketing strategy of two E-Commerce. Where in the marketing strategy can be observed in terms of prices, products, promos and service offered. This research method uses qualitative methods based on literature results through sources from previous research results by discussing data based on theory 15 informants. This study aims to determine the E-Commerce application that is in great demand by the respondents in terms of its marketing strategy. The results of this study indicate that the most widely used E-Commerce based on its marketing strategy is shopee. this can be seen in terms of the price offered, the promotions provided, the products sold according to the prcie, and the service provided.